Decay Polymers and Their Destructions - Khidirova., Y. Kh.; Ziyodullayev., N. Q. (Research Parks Publishing LLC, 2023)
The economic and social development of our country is developing with rapid pictures in accordance with the directions of the chemical industry, especially technical progress, which provides all sectors of the national economy with local raw materials and materials.